Bài 1: Tìm y: 7,75 - ( 0,5 × y : 5 - 6,2 ) = 1,75
tìm y;7,75-(0,5*y:5-6,2)=1,75
7,75-(0,5xY:5-6,2) = 1,75
(0,5xY :5-6,2)=7,75-1,75
(0,5xY:5-6,2)= 6
0,5xY:5=6+6,2
0,5xY:5= 12,2
0,5xY= 12,2x5
0,5xY=61
Y=61:0,5
Y=122
vậy Y= 122
7,75-(0,5*y:5-6,2)=1,75
0,5*y:5-6,2=7,75-1,75
0,5:5*y-6,2=6
0,1*y-6,2=6
y-6,2=6:0,1
y-6,2=60
y=60+6,2
y=66,2
6,3 x y + 3,7 x y = 100
7,75-(0,5 x y : 5 - 6,2) = 1,75
Tìm y
6,3 x y + 3,7 x y = 100
(6,3 + 3,7) x y = 100
10 x y = 100
y = 100 : 10
y = 10
7,75 - (0,5 x y : 5 - 6,3) = 1,75
0,5 x y : 5 - 6,2 = 7,75 - 1,75
0,5 x y : 5 - 6,2 = 6
0,5 x y : 5 = 6 + 6,2
0,5 x y : 5 = 12,2
0,5 x y = 12,2 x 5
0,5 x y = 61
y = 61 : 0,5
y = 122
\(6,3\times y+3,7\times y=100\)
\(\Rightarrow y\times\left(6,3+3,7\right)=100\)
\(\Rightarrow y\times10=100\)
\(\Rightarrow y=100:10=10\)
\(7,75-\left(0,5\times y:5-6,2\right)=1,75\)
\(\Rightarrow0,5\times y:5-6,2=7,75-1,75\)
\(\Rightarrow0,5\times y:5-6,2=6\)
\(\Rightarrow0,5\times y:5=6+6,2\)
\(\Rightarrow0,5\times y:5=12,2\)
\(\Rightarrow y:5=12,2:0,5\)
\(\Rightarrow y:5=24,4\)
\(\Rightarrow y=24,4\times5=122\)
Tìm y :
6,3 x y + 3,7 x y = 100
(6,3 + 3,7) x y = 100
10 x y = 100
y = 100 : 10
y = 10
Vậy y = 10
7,75 - (0,5 x y : 5 - 6,3) = 1,75
0,5 x y : 5 - 6,2 = 7,75 - 1,75
0,5 x y : 5 - 6,2 = 6
0,5 x y : 5 = 6 + 6,2
0,5 x y : 5 = 12,2
0,5 x y = 12,2 x 5
0,5 x y = 61
y = 61 : 0,5
y = 122
Vậy y = 122
đố nhé:tìm y:7,75-[0,5x y :5 -6,2]=1,75
=> 0,5*y:5-6,2=7,75-1,75
=> 0,5*y:5=6+6,2
=> 0,5*y=12,2x5
=> 0,5*y=61
=> y=61:0,5
=> y= 122
tìm y: 7,75 - (0,5 x y : 5 -6,2) = 5
y : 6 x 7,2 + 1,3 x y + y : 2 + 15 = 19,95
\(7,75-\left(0,5\times y\div5-6,2\right)=5\)
\(0,5\times y\div5-6,2=7,75-5=2,75\)
\(0,5\div5\times y-6,2=2,75\)
\(0,1\times y=2,75+6,2=8,95\)
\(\dfrac{1}{10}y=8,95\)
\(y=8,95\times10=89,5\)
\(y\div6\times7,2+1,3\times y+y\div2+15=19,95\)
\(1,2\times y+1,3\times y+0,5y=19,95-15=4,95\)
\(y\left(1,2+1,3+0,5\right)=4,95\)
\(2y=4,95\)
\(y=4,95\div2=2,475\)
1
a. x:6 .7,2+1,3.x+x:2+15=19,95
b. 1:(3,8.x-57/19 +3)=1,75
c. 7,75-(0,5.x:-6,2)=5
1) ( 4/5 : 6/5 + 1/5 : 1/\(x\)) x 30 - 26 = 54
2) 6,3 x y + 3,7 x y = 100
3) 7,75 - ( 0,5 x y : 5 – 6,2 ) = 1,75
4) (8/5 - 1/2 x \(x\)/5 ) :1/5 = 4
5) (\(x\)- 1/2 ) x 5/3 = 7/4 - 1/2
Giải biểu thức sau :
3 x X - 0,8 + 14,5 = 15
X
7,75 - ( 0,5 x y : 5 - 6,2 ) = 1,75
Tính bằng cách hợp lý ( nếu có thể ) : 101 x 789 + 456 x 128 - 789 + 912 x 436
Bài 2 : Tìm x , biết :
a , (X - 2,5) x 1,2 = 6,216
b , X : 8 + X x 8 - 56,78 = 69,11 x 2
c , 7,75 - (0,5X : 5 - 6,2) = 1,75
a) ( x - 2,5 ) x 1,2 = 6,216
( x - 2,5 ) = 6,216 : 1,2
( x - 2,5 ) = 5,18
x = 5,18 + 2,5
x = 7,68
b) X : 8 + X x 8 - 56,78 = 69,11 x 2
X : 8 + X x 8 - 56,78 = 138,22
X : 8 + X x 8 = 138,22 + 56,78
X : 8 + X x 8 = 195
X x 1/8 + X x 8 = 195
X x ( 1/8 + 8 ) = 195
X x 65/8 = 195
X = 195 : 65/8
X = 24
c. 7,75 - (0,5X : 5 - 6,2) = 1,75
0,5x:5-6,2=7,75-1,75
0,5x:5-6,2=6
0,5x:5=6+6,2
0,5x:5=12,2
0,5x=12,2x5
0,5x=61
x=61:0,5
x=122
a) ( x - 2,5 ) x 1,2 = 6,216
( x - 2,5 ) = 6,216 : 1,2
( x - 2,5 ) = 5,18
x = 5,18 + 2,5
x = 7,68
b) X : 8 + X x 8 - 56,78 = 69,11 x 2
X : 8 + X x 8 - 56,78 = 138,22
X : 8 + X x 8 = 138,22 + 56,78
X : 8 + X x 8 = 195
X x 1/8 + X x 8 = 195
X x ( 1/8 + 8 ) = 195
X x 65/8 = 195
X = 195 : 65/8
X = 24
c. 7,75 - (0,5X : 5 - 6,2) = 1,75
0,5x:5-6,2=7,75-1,75
0,5x:5-6,2=6
0,5x:5=6+6,
20,5x:5=12,2
0,5x=12,2x5
0,5x=61
x=61:0,5
x=122